Penerapan E-Book Kibashi pada Pembelajaran Pendidikan Agama Islam di SDN Rancamulya Kelas 5 - Khoirunnisa, Aliya; Niar, Siti Aisyah; Nabila, Cindy Tia; Aeni, Ani Nur (ISLAMIKA, 2024)
This research is motivated by the importance of using learning media in the learning process. Researchers use an e-book called "Kibashi" as a learning medium that will be carried out. This research was conducted with the aim of evaluating learning media significantly in the context of technology that continues to develop today. The research method used was descriptive qualitative, using the D & D method. The subjects of this research were class V students at SDN Rancamulya, Sumedang. The results of surveys and observations show a positive response, highlighting the important role of educators in integrating technology in the learning process, especially in the use of learning media. However, the research results also reveal that there are still few educators who use e-book-based learning media. Thus, we are interested in discussing this topic further, with the hope that the adoption of e-book-based learning media such as Kibashi has great potential in improving the quality of the learning process. And we hope that this research can provide valuable insight for educators and others about the benefits of the "Kibashi" e-book.